Igh Locus Polymorphism May Dictate Topological Chromatin Conformation and V Gene Usage in the Ig Repertoire - Kenter, Amy L.; Watson, Corey T.; Spille, Jan-Hendrik (Frontiers in Immunology, 2021)
Vast repertoires of unique antigen receptors are created in developing B and T lymphocytes. The antigen receptor loci contain many variable (V), diversity (D) and joining (J) gene segments that are arrayed across very large genomic expanses and are joined to form variable-region exons of expressed immunoglobulins and T cell receptors. This process creates the potential for an organism to respond to large numbers of different pathogens. Here, we consider the possibility that genetic polymorphisms with alterations in a vast array of regulatory elements in the immunoglobulin heavy chain (IgH) locus lead to changes in locus topology and impact immune-repertoire formation.